FACEBOOK GROUPS AS A SUPPORTING TOOL FOR LANGUAGE CLASSROOMS - Ekoc, Arzu (ANADOLU UNIV, 2014)
This paper attempts to present a review of Facebook group pages as an educational tool for language learning. One of the primary needs of foreign language learners is to gain the opportunity to use the target language outside the classroom practice. Social media communication provides occasions for learners to receive input and produce output while engaging in negotiation of meaning. In line with this point, teachers can instigate class group pages in the social media in an attempt to provide a space for practice and communication free of the traditional pedagogic concerns of a typical classroom. The distinctive discursive behaviour of Facebook group pages helps one to achieve that attempt. In light of these views, the researcher, in this study, formed a group page to understand the dynamics of social media environment as a supporting tool for language classrooms. This paper addresses various features which make social media a unique place to contribute to the sense of class community and collaboration outside the classroom. The face-to face classroom is a controlled communication event, that is, teachers and students are required to be in the classroom at the same time but a teacher's use of Facebook is an attempt to communicate with students outside of that controlled environment where teachers can meet students in their territory. When compared to its disadvantages, the advantages of setting a class group page on the social media outweigh. Students can feel motivated to contribute to an online community if they subsequently receive support or help. It also leads students to feel that they are being supported by a whole portion of their class community and promotes students' desire to maintain a valued relationship with others. Students continue developing and strengthening relationships with others.
Keywords: Social media; facebook groups; digital literacies; language learning; Education & Educational Research